A Preliminary Checklist of Birds in Azmat Abad Village Thanna Mandi District Rajouri of, Jammu and Kashmir - Sajid Ali; Pragya Shrivastava (Research Parks Publishing LLC, 2021)
Birds play an important role in the ecosystem as long-distance pollinators, scavengers as well as biocontrol agents of various crop pests and thus to be considered as bio-indicators. Different birds have different habitats, some are aerial, some are terrestrial, some are aquatic, some lives near the bank of the reservoir. In this survey, the bird diversity has been recorded for the first time as a preliminary checklist purpose of Azmat Abad Village of Thelsil Thanna Mandi of District Rajouri of J&K The Field survey was done from Agust to October 2020. Total 9 species of terrestrial Birds have been recorded. The preliminary checklist is provided for the undertaking of future research and conservation as well as management on the bird’s diversity of Azmat Abad village